Ultraviolet radiation exposure and serum vitamin D levels in young children. (18th June 2014) - Ramankutty, Padmaja; de Klerk, Nicholas H; Miller, Margaret; Fenech, Michael; O'Callaghan, Nathan; Armstrong, Bruce K; Milne, Elizabeth
<x xml:space="preserve">Abstract</x> Aim Health benefits of adequate vitamin D levels in the blood include better bone health and a reduced incidence of a range of chronic diseases and infections. Ultraviolet (UV) radiation exposure from the sun is the main source of vitamin D; however, such exposure, especially from a young age, is also a potential risk factor for skin cancer. The current study examined the association of UV exposure with vitamin D production in young children to determine the period of weekly exposure prior to blood testing that affected serum 25‐hydroxyvitamin D (25(OH)D) levels. Methods Between 2009 and 2011, healthy children aged 3, 6 and 9 years were recruited from the community for a cross‐sectional study of nutritional factors and DNA damage. Parents of 464 children provided information on the children's average weekly sun exposure and level of sun protection during each of the 16 weeks before blood sample collection by a domiciliary phlebotomist. Results Serum 25(OH)D levels were best predicted from UV exposure during the week before blood collection for samples drawn in autumn, summer or spring. For samples drawn in winter, serum 25(OH)D levels were best predicted by UV exposure during the 2 weeks before blood collection. Conclusions Consistent weekly sun exposure may be beneficial for young children, especially in winter, to maintain healthy vitamin D levels in the blood. However, confirmation of these results is needed before their public health significance can be fully evaluated.